Energy-Efficient Dual-Iteration Power Allocation for Two-Phase Relay System with Massive Antennas - Long Zhao; Wei Xiang; Jie Mei; Hui Zhao; Hang Long; Lin Li (International Journal of Antennas and Propagation)
This paper considers the scenario where multiple source nodes communicate with multiple destination nodes simultaneously with the aid of an amplify-and-forward relay equipped with massive antennas. In order to achieve optimal energy efficiency (EE) of the entire relay system, this paper investigates the power allocation problem for the multiple pairs of nodes at both the source nodes and the relay node, where the relay employs the backward and forward zero-forcing filters. Since the EE optimization problem cannot be solved analytically, we propose a two-phase power allocation method. Given power allocation of one phase, the optimal power allocation is derived for the other phase. Furthermore, two dual-iteration power allocation (DIPA) algorithms with performance approaching that of optimal EE are developed based on the instantaneous and statistic channel state information, respectively. Numerical results show that the proposed DIPA algorithms can greatly improve EE while guaranteeing spectrum efficiency (SE) when compared with the equal power allocation algorithm. Moreover, both algorithms suggest that deploying a rational number of antennas at the relay node and multiplexing a reasonable number of node pairs can improve on the EE and SE.